2020
DOI: 10.1111/ajsp.12419
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude as a protective factor against anxiety and depression among Chinese adolescents: The mediating role of coping flexibility

Abstract: Gratitude is a crucial element of mental health and wellbeing. But the underlying mechanism by which gratitude is negatively associated with anxiety and depression has been underinvestigated. The current study aimed to examine the associations among gratitude, anxiety, and depression in Chinese adolescents, with a focus on coping flexibility as an individual factor mediating their associations. To do this, 492 middleschool students in China were surveyed. Subsequently, a mediation model based on the broaden-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
(125 reference statements)
1
22
0
1
Order By: Relevance
“…Coping resources in the face of a stressful event such as preterm birth and mothering NICU hospitalized infants, can be viewed through the lens of the Transactional Stress Theory, which was developed by Lazarus and Folkman (1984) and is widely applied in the context of depression (e.g., Sun et al., 2020). According to this theory, stress is not an objective situation, but a subjective interpretation attributed to a given event, that is, primary appraisal .…”
Section: Introductionmentioning
confidence: 99%
“…Coping resources in the face of a stressful event such as preterm birth and mothering NICU hospitalized infants, can be viewed through the lens of the Transactional Stress Theory, which was developed by Lazarus and Folkman (1984) and is widely applied in the context of depression (e.g., Sun et al., 2020). According to this theory, stress is not an objective situation, but a subjective interpretation attributed to a given event, that is, primary appraisal .…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical evidence supported the effect of gratitude on depressive symptoms. First, some cross-sectional surveys have found the negative relationship between gratitude and depressive symptoms (Lambert, Fincham, & Stillman, 2012;Liang et al, 2018;Lin, 2015b;Simon, 2016;Sun, Sun, Jiang, Jia, & Li, 2020;Wu, Chi, Lin, & Du, 2018;Zhang & Wang, 2019). Second, several studies have found that gratitude interventions can enhance people's gratitude and decrease people's depressive symptoms (Cheng, Tsui, & Lam, 2015;Cregg & Cheavens, 2021;Wood, Maltby, Gillett, Linley, & Joseph, 2008).…”
Section: Antecedent Modelmentioning
confidence: 99%
“…Thus, gratitude may reduce people's depressive symptoms. However, most of the existing studies have found a negative relation between gratitude and depressive symptoms in the general populations (Lambert, Fincham, & Stillman, 2012;Liang et al, 2018;Lin, 2015b;Simon, 2016;Sun, Sun, Jiang, Jia, & Li, 2020;Wu, Chi, Lin, & Du, 2018;Zhang & Wang, 2019), so less is known about the causal link between gratitude and depressive symptoms among Chinese nurses. Exploring the causal relationship between gratitude and depressive symptoms can enrich the research of gratitude and depressive symptoms and find appropriate interventions that reduce depressive symptoms and improve well-being among Chinese nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The coping flexibility hypothesis [ 10 ] posits that greater coping flexibility will produce more adaptive outcomes in psychological and physical responses to stressors [ 14 , 15 ]. This hypothesis, which is based on the principles of the dual-process theory, has been supported through studies done in multiple countries, such as the United States [ 17 , 18 , 19 , 20 , 21 ], the United Kingdom [ 22 ], Poland [ 23 , 24 ], Australia [ 19 ], Canada [ 25 ], China [ 19 , 26 , 27 ], Hong Kong [ 28 , 29 ], Japan [ 10 , 11 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], India [ 20 , 37 ], Malaysia [ 38 ], and Israel [ 39 , 40 ]. For example, greater coping flexibility was found to be associated with lower change scores from baseline to reactivity in heart rate and systolic blood pressure responses during a stressful cognitive task, but not during a non-stressful task [ 33 ], indicating that greater coping flexibility reduces cardiovascular reactivity to a stressful task.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a principal response to chronic stress [ 41 , 42 ]. Many studies have demonstrated that lower coping flexibility based on the dual-process theory is associated with lower levels of depression [ 10 , 17 , 19 , 21 , 23 , 26 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. For example, both abandonment and re-coping were found to explain a unique amount of the variance in depressive symptoms after 14 weeks from baseline, beyond coping flexibility as measured by other approaches (i.e., coping repertoire, coping variability, and coping fitness) as well as typical coping strategies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%